The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1001/jamainternmed.2015.2609
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Incontinence Before and After Bariatric Surgery

Abstract: IMPORTANCE Among women and men with severe obesity, evidence for improvement in urinary incontinence beyond the first year after bariatric surgery-induced weight loss is lacking.OBJECTIVES To examine change in urinary incontinence before and after bariatric surgery and to identify factors associated with improvement and remission among women and men in the first 3 years after bariatric surgery. DESIGN, SETTING, AND PARTICIPANTSThe Longitudinal Assessment of Bariatric Surgery 2 is an observational cohort study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 44 publications
2
48
1
11
Order By: Relevance
“…Subak et al found that weight loss after bariatric surgery was associated with substantially decreased urinary incontinence during 3 years. 13 Further research is needed of the role of weight loss in UUI refractory to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Subak et al found that weight loss after bariatric surgery was associated with substantially decreased urinary incontinence during 3 years. 13 Further research is needed of the role of weight loss in UUI refractory to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, female UI is also related with other factors such as parity, type of delivery, previous hormone therapy and urogenital surgery, constipation, existence of pelvic floor disorders or other chronic diseases [29,31,[38][39][40]. Non-surgical weight loss interventions (diet, exercise or a combination of both) may improve female UI [41] and recently it has been shown that under extreme obese conditions, bariatric surgery has been proposed to improve urinary continence [42].…”
Section: Discussionmentioning
confidence: 99%
“…The investigators of the Longitudinal Assessment of Bariatric Surgery 2 recently published their 3 year follow-up data. 68 Prevalent UI, defined as at least weekly UI episodes, was 49.3% at baseline in the women, 18.3% at 1 year (mean weight loss 29.5%), and 24.8% at 3 years. Similar optimistic findings were reported by the investigators of the Program to Reduce Incontinence by Diet and Exercise (PRIDE), even with modest weight loss defined as 5–10% of body weight.…”
Section: Phase Iii: Intervening Factors For Pelvic Floor Disordersmentioning
confidence: 93%